How Bad Is a Near-Miss in Driving? A Proposed Metric Based on Reenactment Variability. (July 2013) - Sheridan, Thomas B.
How bad is a near miss? After the fact, the collision probability is zero. The real concern is what might have happened under slightly different conditions. In this article, I propose a safety measure commensurate with probability of collision for an event reenactment that depends on estimating the variability of closest proximity between vehicles. Example calculations are provided for several combinations of vehicles passing, stopping, or converging. Until recently, this radically different approach has been impractical, but new technology to measure and store proximity data changes that outlook. Various means are suggested by which the metric can be used to enhance driver safety.